Future Arctic sea ice loss reduces severity of cold air outbreaks in midlatitudes. Issue 6 (18th March 2016) - Ayarzagüena, Blanca; Screen, James A.
Abstract: The effects of Arctic sea ice loss on cold air outbreaks (CAOs) in midlatitudes remain unclear. Previous studies have defined CAOs relative to the present‐day climate, but changes in CAOs, defined in such a way, may reflect changes in mean climate and not in weather variability, and society is more sensitive to the latter. Here we revisit this topic but applying changing temperature thresholds relating to climate conditions of the time. CAOs do not change in frequency or duration in response to projected sea ice loss. However, they become less severe, mainly due to advection of warmed polar air, since the dynamics associated with the occurrence of CAOs are largely not affected. CAOs weaken even in midlatitude regions where the winter mean temperature decreases in response to Arctic sea ice loss. These results are robustly simulated by two atmospheric models prescribed with differing future sea ice states and in transient runs where external forcings are included. Key Points: CAOs are identified relative to the climatology of each period in contrast to previous work CAOs become less severe in response to sea ice loss, but their frequency and duration do not change The response of midlatitude CAOs to sea ice loss is largely governed by thermodynamical processes